The Road Not Taken: What Developmental Psychology Might Learn From Darwin’s Insights Concerning Sexual Selection - Goetz, Stefan M. M.; Weisfeld, Carol Cronin; Weisfeld, Glenn E. (Frontiers in Psychology, 2022)
Developmental Psychology is the branch of psychology that studies, not only human behavior, but how and why human behavior changes over time. This essay seeks to review to what extent Developmental Psychology has failed to perceive human behavior through the lens of evolutionary theory in general, and in particular sexual selection as first described by Darwin and later elaborated on by many, including Robert Trivers and Geoffrey Miller; the essay asserts that this failure has resulted in many wrong turns and missed opportunities. In some cases, major developmental theorists (e.g., Freud, Erikson) were bedeviled by sex-based differences which they saw but could not explain and which compromised the parsimony of their stage theories. In the case of stage theories of moral development, some major theorists (e.g., Piaget, Kohlberg) were able to offer simpler explanations of moral development only by limiting their studies to male subjects. And, while Developmental Psychology textbooks thoroughly describe sex differences in the timing of morphological changes in puberty, writers seldom discuss why the timing is different in the two sexes, universally, and functionally. On the other hand, several domains of developmental focus, including play, mate choice, parenting, and spatial cognition, have seen successful research efforts that utilized sexually selected predispositions as foundational assumptions. The essay concludes with a discussion of how a more evolutionary and functional view of human behavior might move the field of Developmental Psychology to an even more robust and accurate understanding of how humans change over the course of a lifetime.